Leveraging on multi-utility waterbodies to sustainably produce aquatic foods in India - Shenoy, Neetha; Dubey, Sourabh Kumar (WorldFish, 2022)
Ponds are a key component of the rural agricultural landscapes of Odisha and one of the state's bounteous aquatic resources. The government of Odisha has set a unique example by using adaptive governance strategies to manage community waterbodies through aquatic farming. Despite not being as well protected by law or policy as other waterbodies, ponds offer environmentally friendly answers to some of the most significant issues associated with water management and climate change.